Long-Term Use of Lipid-Lowering Drugs Slows Progression of Carotid Atherosclerosis The Tromso Study 1994 to 2008 - Herder, Marit; Arntzen, Kjell Arne; Johnsen, Stein Harald; Eggen, Anne Elise; Mathiesen, Ellisiv B. (Arteriosclerosis, Thrombosis, and Vascular Biology, 2013)
This paper is part of Marit Herder's doctoral thesis, available in Munin at http://hdl.handle.net/10037/5723 Data on the effect of lipid-lowering drugs (LLD) on carotid atherosclerosis outside clinical trials are limited. The aim of this study was to determine the effect of LLD on change in carotid intima media thickness and total plaque area in a general population. Subjects were 1532 women and 1442 men who participated in a longitudinal population-based study with ultrasound examination of intima media thickness and total plaque area in the right carotid artery at baseline and after 13 years follow-up. Long-term use of LLD was defined as use for >5 years, any-time use of LLD was defined as use at baseline or at 6 years or at 13 years of follow-up. In multivariable models adjusted for age, sex, systolic blood pressure, total cholesterol, high-density lipoprotein cholesterol, prevalent cardiovascular disease, and daily smoking, long-term use of LLD had a protective effect on progression of both intima media thickness (β=–0.0387 mm; P=0.002) and total plaque area (β=–0.400 mm2; P=0.006). There was a weaker protective effect of any-time use of LLD on progression of intima media thickness (β=–0.024 mm; P=0.046) and total plaque area (β=–0.318 mm2; P=0.06). LLD protected against progression of carotid atherosclerosis. The protective effect was strongest in long-term users.